(untitled) (Hematology Meeting Reports, 2009)
Panobinostat is a novel cinnamic hydroxamic acid pan-deacetylase inhibitor able to induce hyperacetylation of lysine residues on both histone and non-histone targets in cancer cells. Panobinostat is currently in clinical development, as both an intravenous and oral formulation, across multiple tumor types, and as proof of principle has resulted in prolonged histone hyperacetylation in tumor cells along with impressive anti-tumor activity in phase I and II trials, in particular T cell lymphomas, Hodgkin lymphoma and myeloid malignancies. Initial concerns regarding cardiac toxicities appear to have been answered by alterations in dose scheduling. Future studies may help unravel molecularly- or cytogenetically- defined patient sub-groups who are most likely to benefit from panobinostat, either as a single agent, or, ultimately more likely, in combination with other therapies.